Single transient intraocular pressure elevations cause prolonged retinal ganglion cell dysfunction and retinal capillary abnormalities in mice. (December 2020) - Tao, Xiaofeng; Sigireddi, Rohini R.; Westenskow, Peter D.; Channa, Roomasa; Frankfort, Benjamin J.
Abstract: Transient intraocular pressure (IOP) elevations are likely to occur in certain forms of glaucoma and after intravitreal injections to treat various retinal diseases. However, the impact of these transient IOP elevations on the physiology of individual retinal ganglion cells (RGCs) is unknown. In this report, we explore how transient IOP elevations in mice affect RGC physiology, RGC anatomy, and retinal arteriole and capillary structure. Transient IOP elevation was induced in 12-week old wild type C57BL6J mice by injecting sodium hyaluronate into the anterior chamber. IOP was measured immediately after the injection and again 1 and 7 days later. Average peak IOP after injection was ~50 mmHg and subsequent IOPs returned to normal. RGC physiology was assessed with a multielectrode array (MEA) by calculating a spike triggered average (STA) at the same time points. RGC counts and retinal vascular structure were assessed 14 days after injection with immunohistochemistry to label RGCs and blood vessels. Transient IOP elevation caused a marked reduction of scotopic STA presence and delayed center and surround STA peak times that did not recover. Transient IOP elevation also caused a reduced photopic receptive field size and spontaneous firing rate, both of which showed some recovery with time. Transient IOP elevation also induced vascular remodeling: the number of capillary branches was decreased within the superficial and intermediate vascular plexi. RGC counts, retinal arteriole diameter, and deep capillary plexus branching were unaffected. These previously unappreciated findings suggest that transient IOP elevation may cause unrecognized and potentially long-term pathology to RGCs and associated neurovascular units which should be accounted for in clinical practice. Highlights: ∙ We transiently elevated IOP to high levels in mice. ∙ We assessed RGCs function at three time points after IOP elevation. ∙ We assessed retinal vascular anatomy and RGC numbers at one time point after IOP elevation. ∙ Multiple aspects of RGC function were abnormal after IOP elevation, and these had different patterns of recovery with time. ∙ Specific retinal vascular plexi had reduced numbers of capillary branches.